Dylematy wyborcy. Czynniki wpływające na zachowania w kampanii prezydenckiej i samorządowej w 2010 roku - Alberski, Robert (Political Preferences, 2011)
This part of the report discusses three questions, included in the questionnaire about electoral behavior during presidential and local elections in 2010. First question asks about the time, when the voter made his decision for which candidate he would vote for in the First round in the Presidential election. Second question is about the factors, that decide in choos- ing particular electoral committee in Local elections and third - about the problem of how big and stable is negative electorate of Polish political parties. As can be seen from presented data, majority of voters was sure of their political preferences long before the beginning of Presi- dential campaign and those, who made their decision during it, in most cases, in it's first phase. The mobility of Polish electorate is reduced, also because of the largeness and mutual pen- etration of negative electorate and effectiveness of political agitation is also limited. Because of that voters political preferences are relatively stable, despite the Smoleńsk Crash and in- creasingly intense competition of party elites.